TOOK THE RACE PREPARATION AND PLANNING IT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article is devoted to the preparation of athletes for special events and physical preparation for public life, as well as one of the most important aspects.